2015
DOI: 10.1007/s13197-014-1704-0
|View full text |Cite
|
Sign up to set email alerts
|

Reactivity of phenolic compounds towards free radicals under in vitro conditions

Abstract: The free radical scavenging activity and reducing power of 16 phenolic compounds including four hydroxycinnamic acid derivatives namely ferulic acid, caffeic acid, sinapic acid and p-coumaric acid, benzoic acid and its derivatives namely protocatechuic acid, gallic acid and vanillic acid, benzene derivatives namely vanillin, vanillyl alcohol, veratryl alcohol, veratraldehyde, pyrogallol, guaiacol and two synthetic antioxidants, butylated hydroxy anisole (BHA) and propyl gallate were evaluated using 1,1-Dipheny… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

11
174
0
1

Year Published

2015
2015
2024
2024

Publication Types

Select...
5
3
1

Relationship

1
8

Authors

Journals

citations
Cited by 263 publications
(186 citation statements)
references
References 48 publications
11
174
0
1
Order By: Relevance
“…However BHA did not exhibit any radical scavenging effect at these concentrations. Even though vanillin is not a very good antioxidant it was chosen as a standard, as superoxide radical scavenging and antiglycation end product inhibition has been reported [6,27] for vanillin and for the fact that it was identified as one of the phenolic components in PA [3,8,31]. The redox potentials of DCPAP and CPAP are presumed to be lower than the oxy-radical, superoxide radical anion [36] as they are good scavengers of these oxy radicals.…”
Section: Superoxide Radical Scavengingmentioning
confidence: 99%
See 1 more Smart Citation
“…However BHA did not exhibit any radical scavenging effect at these concentrations. Even though vanillin is not a very good antioxidant it was chosen as a standard, as superoxide radical scavenging and antiglycation end product inhibition has been reported [6,27] for vanillin and for the fact that it was identified as one of the phenolic components in PA [3,8,31]. The redox potentials of DCPAP and CPAP are presumed to be lower than the oxy-radical, superoxide radical anion [36] as they are good scavengers of these oxy radicals.…”
Section: Superoxide Radical Scavengingmentioning
confidence: 99%
“…The role of free radicals and reactive oxygen species (ROS) in the pathogenesis of human diseases such as cancer, aging and atherosclerosis has been reported [5] and many plant phenolic compounds possess potent antioxidant and free radical scavenging activities [6].…”
Section: Introductionmentioning
confidence: 99%
“…It has been suggested that free radical scavengers protect skin from UVB‐induced damage by increasing the antioxidant balance of the skin (Shindo, Witt, & Packer, ). In general, hydroxylated cinnamates are better scavengers than their benzoate counterparts (Mathew, Abraham, & Zakaria, ). In the present study, we also found that hydroxylated cinnamate derivatives such as CA and SA had a higher protective effect than the other phenolic acids against UVB‐irradiation in the dermal fibroblasts.…”
Section: Resultsmentioning
confidence: 99%
“…For understanding of antioxidant behaviour of foxtail millet, it is important to know not only total phenolic content, but also the phenolic profile. The antioxidant efficacy of phenolics is diverse and depends on many factors, such as the number of hydroxyl groups bonded to the aromatic ring, the site of bonding and mutual position of hydroxyls in the aromatic ring, character of other substituent and their position in relation to the hydroxyl groups (Mathew et al 2015). In our study, the red genotype 0011 has higher content of p-coumaric and ferulic acid-cinnamic acid derivatives in comparison to the yellow genotype Slovenský, but the lower antioxidant activity.…”
Section: Discussionmentioning
confidence: 99%